Clinical and bacteriological profile of suppurative otitis media in Kinshasa: A descriptive cross-sectional study - Kasonga, BAFUANANSHA Léonard; Tshingamb, KAMIN Yasmin; Kembia, TSHIKOLU Elisée; Ntumba, MALEMBA alain; Pholo, MADIMBALA Jean Paul; Banza, LUKOJI Eric; Mbuyamba, NGOY Jules; Kamwiziku, KUSANZANGANA Guyguy; Lunguyla, METILI Octavie; NYEMBUE , TSHIPUKANE Dieudonné (Orapuh Journal, 2025)
Introduction Suppurative otitis media (SOM) is a predominantly bacterial disease that is common in low-income countries. The bacterial spectrum responsible for SOM and the antibiotic susceptibility patterns vary over time and between regions, necessitating periodic updates to improve disease management.PurposeThis study aimed to determine the clinical and bacteriological profile of SOM in Kinshasa.MethodsThis descriptive cross-sectional study included 71 patients with SOM who were followed at the University Hospital of Kinshasa from April to October 2024. Sociodemographic and clinical data were collected. A middle ear suppuration swab was taken via the external auditory canal near the perforated eardrum. After Gram staining of the samples, inoculation was carried out on various culture media to isolate the bacteria. Finally, an antibiogram was performed using the Kirby-Bauer technique. Statistical data analysis was conducted using SPSS version 27.0.ResultsThe mean age of the patients was 33 ± 21.7 years, with ages ranging from 1 to 82 years. The majority of patients were male (53.5%), while 46.5% were female. Chronic suppurative otitis media (CSOM) was the most prevalent form of the disease, accounting for 67.6% of cases. Otorrhea was unilateral in three-quarters of the patients and was associated with hypoacusis in 69% of cases. Out of the 90 swabs collected, 76% showed microbial growth. Among the positive cultures, 70.6% were Gram-negative bacteria, while 29.4% were Gram-positive. The most frequently isolated bacterium was Pseudomonas aeruginosa, followed by Staphylococcus aureus. Ciprofloxacin demonstrated the highest efficacy against all isolated bacteria, followed by gentamicin.ConclusionSuppurative otitis media is a bacterial infection, and antibiotic therapy should be guided by bacteriological data to develop empiric antibiotic guidelines, prevent bacterial resistance, and reduce the risk of complications.